2020
DOI: 10.1111/jai.14115
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of prey condition and incubation method on mortality, growth and metabolic rate during early life history in lake sturgeon, Acipenser fulvescens

Abstract: Environmental conditions during early life can have a profound impact on developmental trajectory and ultimately ecological fitness of individuals. Therefore, from a conservation perspective it is vital to understand the longer-term implications of early phenotypic development on survival. In this study, we examined the effects of temperature (maintained at 16°C or ambient river temperature), prey condition (live or dead Artemia) and incubation method (tumbling jar or natural hatching over substrate) on the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Lake sturgeon that are used to enhance northern populations are typically reared at the Grand Rapids Fish Hatchery at 16 C with the potential for increasing rearing temperatures in the first year of life to increase growth rates and achieve larger sturgeon prior to release (Bugg et al, 2020). Recent studies have demonstrated that subtle changes in rearing temperature during early development can influence the growth and condition of lake sturgeon prior to a simulated overwintering event, which may influence survival rates (Brandt et al, 2022;Yoon et al, 2019Yoon et al, , 2020. However, there is little data available concerning the effects of exposures to elevated temperatures during early development on adaptive responses to cold during the first winter of life.…”
mentioning
confidence: 99%
“…Lake sturgeon that are used to enhance northern populations are typically reared at the Grand Rapids Fish Hatchery at 16 C with the potential for increasing rearing temperatures in the first year of life to increase growth rates and achieve larger sturgeon prior to release (Bugg et al, 2020). Recent studies have demonstrated that subtle changes in rearing temperature during early development can influence the growth and condition of lake sturgeon prior to a simulated overwintering event, which may influence survival rates (Brandt et al, 2022;Yoon et al, 2019Yoon et al, , 2020. However, there is little data available concerning the effects of exposures to elevated temperatures during early development on adaptive responses to cold during the first winter of life.…”
mentioning
confidence: 99%
“…As the environment during early life could significantly influence phenotypic development in lake sturgeon (Dammerman et al, 2015 ), metabolic rate data in this analysis were used from age‐0 lake sturgeon that were raised under the same environmental conditions of temperature (16°C), dissolved oxygen (100%), and without substrate in rearing tanks. The data analyzed here include previously published and unpublished data (Bugg et al, 2020 , 2023 ; Yoon et al, 2020 , 2021 ; Yoon, Amjad, et al, 2022 ; Yoon, Bugg, et al, 2022 ; Yoon, Deslauriers, & Anderson, 2019 ; Yoon, Deslauriers, Enders, et al, 2019 ; Yoon, Groening, et al, 2022 ; Yoon, Laluk, et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Optimization of the production requires extensive evaluation studies. Therefore, research on nutritional factors including feeding rates (Deng et al, 2003; Jafari et al, 2018), co‐feeding methods, feed particle sizes (Rónyai & Feledi, 2012), prey condition, and incubation method (Yoon et al, 2020), as well as research on culture conditions such as rearing temperature, appropriate water velocity (Mrnak et al, 2020; Poletto et al, 2018) and stocking density (Oprea & Oprea, 2009) are essential to overcome the bottlenecks and optimize the aquaculture production.…”
Section: Introductionmentioning
confidence: 99%